Effects of Early Initiation of High-Dose Dexamethasone Therapy on Pro-Inflammatory Cytokines and Mortality in LPS-Challenged Mice - Son, Ji Young; Kwack, Won Gun; Chung, Eun Kyoung; Shin, Sooyoung; Choi, Yeo Jin (Healthcare (Switzerland), 2022)
This study aims to explore the effects of early dexamethasone therapy at low to high doses on the survival and inflammatory responses in lipopolysaccharide (LPS)-challenged mice. We performed two-series experiments to explore the impact of early dexamethasone therapy at different doses (0.5 mg/kg, 1.5 mg/kg, and 5 mg/kg; PO) on pro-inflammatory cytokine levels, including tumor necrosis factor-alpha (TNF-α) and interleukin-6 (IL-6), as well as survival in LPS-treated mice (10 mg/kg, IP). Dexamethasone was administered daily from 24 h before and 5 days after LPS challenge. Dose-dependent improved survival was demonstrated with dexamethasone (p < 0.05). Body weight was significantly decreased within 24 h of LPS injection, with significantly greater weight loss in the dexamethasone groups (p < 0.05). Weight changes were significantly associated with the days after LPS administration (p < 0.01), but not with the dexamethasone dose (p > 0.05). Mice treated with high-dose dexamethasone (5 mg/kg) had a significantly lowered serum TNF-α (134.41 ± 15.83 vs. 408.83 ± 18.32) and IL-6 (22.08 ± 4.34 vs. 91.27 ± 8.56) compared with those without dexamethasone. This study provides essential insights that the suppression of early-phase hyperactivation of pro-inflammatory activities through the early initiation of high-dose dexamethasone therapy increases sepsis-related prognosis.
Keywords: acute inflammation; corticosteroid; dexamethasone; lipopolysaccharide; sepsis